2x-7+8x-3=4x+6x+10

Simple and best practice solution for 2x-7+8x-3=4x+6x+10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-7+8x-3=4x+6x+10 equation:


Simplifying
2x + -7 + 8x + -3 = 4x + 6x + 10

Reorder the terms:
-7 + -3 + 2x + 8x = 4x + 6x + 10

Combine like terms: -7 + -3 = -10
-10 + 2x + 8x = 4x + 6x + 10

Combine like terms: 2x + 8x = 10x
-10 + 10x = 4x + 6x + 10

Reorder the terms:
-10 + 10x = 10 + 4x + 6x

Combine like terms: 4x + 6x = 10x
-10 + 10x = 10 + 10x

Add '-10x' to each side of the equation.
-10 + 10x + -10x = 10 + 10x + -10x

Combine like terms: 10x + -10x = 0
-10 + 0 = 10 + 10x + -10x
-10 = 10 + 10x + -10x

Combine like terms: 10x + -10x = 0
-10 = 10 + 0
-10 = 10

Solving
-10 = 10

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -8y+6=-9-7y | | x-48=6 | | 5(x+2)-(5x+10)=0 | | 4x+2=10x-1 | | 80*6x=45+32*4x+23x | | (3x+1)(2x-4)-x(6x-7)=0 | | 32=48t+16t^2 | | .25(16x-20)=.5(10x-8) | | 6y-2x=24 | | 5t+5=-2-7t | | 5y-2y=21 | | 15x^2+2x-56=0 | | 4p+5q= | | 8d=-4+12 | | 16(x-64)=32 | | 5k+6=15 | | x^6-12x^4+48x^2-60=0 | | 53x+56/26-69*(85*4)=5 | | 5+2b=10-3b | | 7x+8=64 | | 98-7x=11x+24 | | 12-5*(5-4x)=27 | | 115-6x=30x+23 | | 4p-3=7 | | 6y+3x=24 | | 54-4x=5x+20 | | 8x-3=2c+15 | | x(3x+11)=4 | | 14-10x=142-38x | | 7-7x=207-42x | | 6x+9=-135-10x | | 144-5x=6x-9 |

Equations solver categories